Physical meat quality and chemical composition of the Longissimus thoracis of entire and immunocastrated pigs fed varying dietary protein levels with and without ractopamine hydrochloride. (December 2015) - Needham, T.; Hoffman, L.C.
Abstract: Physical and chemical attributes of the Longissimus thoracis (LT) of 96 PIC © entire (E) and immunocastrated (C) pigs were evaluated. The study followed a 2 × 2 × 3 factorial design where three diets of low, medium and high proteins (7.50, 9.79 and 12.07 g digestible lysine/kg) were fed either with (10 mg/kg) or without ractopamine (RAC) for the last 28 days of growth. Vaccination of C occurred at 16 and 20 weeks and slaughtering at 24 weeks of age. The LTs were analysed for moisture, protein, fat and ash contents as well as CIE L*, a*, b* colour, drip loss, cooking loss and Warner–Bratzler shear force (WBSF). Various sex and protein interactions were observed for LT protein content, L* values and WBSF. Cooking loss was decreased in C and by the medium protein diet. Feeding RAC increased WBSF values, whilst decreasing a* and b* values. However, the differences observed are minor and might be considered negligible when evaluated by a consumer. Highlights: Immunocastrates and entire male pigs were fed RAC with varying dietary proteins. Immunocastration and feeding a medium protein diet decreased cooking loss. RAC increased WBSF and decreased a* and b* values. Sex–protein interactions were observed for muscle protein content, L* values and WBSF. Differences observed were minor thus effects on meat quality are possibly negligible.